The use of acupuncture as a complementary practice for treating patients with Type 2 diabetes mellitus: an integrative literature review - Neca, Cinthia Silva Moura (2021)
Acupuncture is an ancient therapeutic modality in Chinese medicine, which aims to prevent and treat pathologies. The World Health Organization (Ordinance No. 971 of 2016) recognizes that acupuncture works effectively in pathologies such as diabetes mellitus 2 (DMT2) and has been encouraging this complementary therapy. The main effects of acupuncture are associated with blood glucose control, loss of body weight, protection of the function of the pancreas islets, stimulation of production and improvement of insulin resistance. In this paper we describe the follow-up process and evolution in the treatment of people with T2DM using acupuncture through an integrative literature review. Objective: To describe the use of acupuncture as a complementary practice for the treatment of people with DMT2 through an integrative literature review. Methodology: The present work is the result of a literature review of the literature, carried out from March to November 2020. The PubMed / MEDLINE and Scientific Electronic Library Online (SciELO) databases were used with the following descriptor: “Acupuncture and Diabetes mellitus”. Results: Acupuncture performance in DMT2 proved to be effective in treating patients with this chronic disease. Acupuncture treats the person and not the disease itself, as it harmonizes the body and tones the organs. Conclusion: Acupuncture treatment offered to DMT2 patients can bring benefits, improving their health and quality of life. This therapeutic practice has already been implemented in the Unified Health System (SUS), although there is low adherence of patients with T2DM; due to little dissemination and little information about acupuncture.